Energy and Nutrient Density - Wendy J. Dahl; Lauren Foster (EDIS)
Foods for the older adult that has lost weight should target both energy and nutrient density. This 1-page fact sheet provides explanation and examples. Written by Wendy J. Dahl and Lauren Foster and published by the UF Department of Food Science and Human Nutrition, May 2011.